DOI: 10.14264/uql.2016.268
|View full text |Cite
|
Sign up to set email alerts
|

Towards the optimisation of Coarse sprays to reduce drift and improve efficacy in Australian cropping systems

Abstract: The optimisation of Coarse sprays for control of insects, weeds, and diseases in agriculture involves understanding how those technologies are classified and selected for use. Coarse sprays are the focus of this thesis, because Coarse is a spray size classification that balances adequate coverage, while reducing pesticide spray drift. Spray drift is detrimental, and by selecting coarser droplet sprays, spray drift can be minimised. The initial research study in this thesis sought to identify the repeatability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…In order to improve D f and reduce D s , the droplet size spectrum should be increased by selecting a different nozzle type (NT), reducing operating pressure (P) or increasing the nozzle size (S). Several other researchers obtained the same conclusions (Creech et al 2015;Ferguson 2016) and some have even observed that the efficacy with coarser droplets is as good as with finer droplets (Shaw et al 2000). However, the droplet size increase should not exceed 400 µm (medium spray quality) as a limit of droplet run-off on the foliage (Ozkan 2016).…”
Section: Discussionmentioning
confidence: 82%
“…In order to improve D f and reduce D s , the droplet size spectrum should be increased by selecting a different nozzle type (NT), reducing operating pressure (P) or increasing the nozzle size (S). Several other researchers obtained the same conclusions (Creech et al 2015;Ferguson 2016) and some have even observed that the efficacy with coarser droplets is as good as with finer droplets (Shaw et al 2000). However, the droplet size increase should not exceed 400 µm (medium spray quality) as a limit of droplet run-off on the foliage (Ozkan 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Spray pressures of 200 kPa, 300 kPa, 400 kPa, 500 kPa, 600 kPa and 700 kPa and air velocities of 2 m/s, 3 m/s, 4 m/s and 5 m/s were set up. The XR 11003VS was also measured by a method consistent with the ASABE S-572.1 standard in the same laboratory, and it has been used as the ASABE reference nozzle in international spray studies [24][25][26]. The criteria of the size classes were provided by a set of certified reference nozzles.…”
Section: Atomizersmentioning
confidence: 99%
“…The extraction coefficient is generally higher for artificial targets, except for the Brilliant Blue tracer, for filter paper collector, lower than the limit (80%) of extraction established by (ANVISA, 2008) for validation of the analytical methods. The use of artificial collectors for spray characterization is well known using all collector types was useful to properly characterize the sprays and to quantify the differences between each collector type for coverage and droplet density (Ferguson, 2016).…”
Section: Artificial Collectorsmentioning
confidence: 99%